Revitalization Processes of Changing Geospatial in European Cities - Nazaruk, M. M.; Polianskiy, Y. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2019)
Purpose. Brief retrospective analysis of the geographical component of revitalization in European cities, study of the generalized and indirect effect of the revitalization phenomenon on the geospace of urban urban systems. Results. The results of the study of revitalization processes in European cities are presented. European cities are characterized by uneven development, concentration of potential in the capital and some regional centers, as well as the increase of crisis phenomena in the periphery. We are talking about depressed territories, settlements, post-industrial cities or parts of them. That is why we consider it necessary to speak not only about the restoration of potential and improvement of socio-economic indicators in cities, but also about the large-scale implementation of urban space revitalization programs. Approaches to revitalization processes are ideally designed as processes for empowering unused urban space. At the same time, they should be aimed at ensuring the effective use of public and private financed bonds and project funds for projects from the Civic Control Center. The main requirement of the community is to begin the process of updating and involving the administration in these projects. The first round of negotiations between the authorities and society prompted the city to come up with a coherent approach aimed at the target group and at the same time agree on the financial budget and future beneficiaries. In addition to those responsible for urban planning, special roles are assigned to local departments of schools, youth, senior citizens and business development (business, marketing and investor talks). It is these areas of human and financial capital that should be responsible for urban marketing and tourism. The involvement of a restructuring trustee in project planning and development is required. Conclusion. Taking into account the geographical component (in particular the topography, vegetation, green areas), as a result of the revitalization helps to improve the quality of living environment and affects the peculiarities of the geospatial of the city. An important component of the success of a revitalization program must be public participation in discussing and solving problems to ensure sustainable urban development. Studying the experience of European cities in the area of ​​revitalization will give a new impetus to many Ukrainian cities trying to overcome the problems of deprived urban areas, including the historic central districts and mediocrity.